PERAN GANDA: Kajian Buruh Petik Wanita di Perkebunan Teh Gambung Kabupaten Bandung Tahun 2010-2020 - Saskara, Andrianei Arhamah; Sita, Kralawi (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
This research is motivated by the author’s interest in the dual role of female pickers in the Gambung tea plantation located in Mekarsari village, Pasir Jambu district, Bandung regency. The method used is the historical method with four stages, including 1) heuristics, 2) source criticism, 3) interpretation and final steps, and 4) historiography. The subjects or informants in this study were six women picking laborers who had worked in the Gambung tea plantation before 2010. The results showed that most picking laborers in the Gambung tea plantation were women. Participating in picking indirectly gives them a dual role as a reproductive role and a productive role, so it gives them a double burden, both domestic and public. Moreover, the reproductive role of women in social circles and tea-picking workers is often considered a static and permanent role. Even though women work to fulfill household needs, this is not accompanied by a reduction in their burden in the domestic area or a reduction in household work such as washing, cooking, and other household activities. In addition, with their choice to become workers at the Gambung tea plantation, these women picking laborers do not have the freedom of time to carry out all their reproductive roles as a result of their productive roles, which are required to comply with workplace regulations such as hours to go to work, hours to come home, to work and when to holiday.